2009
DOI: 10.1002/qua.22374
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐classical trajectory stereodynamics study of the Li + HF(v = 0, j = 0) → LiF + H reaction

Abstract: ABSTRACT:In this work, quasi-classical trajectory (QCT) calculations for the Li ϩ HF (v ϭ 0, j ϭ 0) 3 LiF ϩ H reaction, on the Aguado-Paniagua2-potential energy surface (AP2-PES) constructed by Aguado et al. (Aguado et al., J Chem Phys 1997, 107, 10085), have been performed to study the vector properties of the products. The dihedral angle distribution P( r ) characterizing the k-k-j correlation and the P( r ) distribution characterizing the k-j correlation are calculated and discussed. Furthermore, the angul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Many theoretical investigations based on the quasiclassical trajectory (QCT), time‐dependent wave packet or quantum dynamics calculation, and density functional theory have been carried out to explore novel reactions. [ 1–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical investigations based on the quasiclassical trajectory (QCT), time‐dependent wave packet or quantum dynamics calculation, and density functional theory have been carried out to explore novel reactions. [ 1–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4] Yuan and Zhao studied the vector properties of the products, and investigated the variation of the rotational alignment with collision energy by QCT calculations on a Aguado-Paniagua2-potential energy surface (AP2-PES). [14] However, to the best of our knowledge, the vibration effects on the vector properties of the title reaction have never been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
“…[20] In 2005, Wecka and Balakrishnan [21] presented the quantum reactive scattering calculations for the scattering process for zero total angular momentum at low and ultralow temperatures. In 2010, Yuan and Zhao [22] studied the vector properties of the products of Li+HF system based on AP2-PES(1997), exploring the dihedral angle distribution 𝑃 (𝜑 𝑟 ) character-izing the 𝑘-𝑘 ′ -𝑗 ′ correlation and the 𝑃 (𝜃 𝑟 ) distribution characterizing the 𝑘-𝑗 ′ correlation. Wangtao and Yue [23] studied the product polarization and isotope effects of reaction F+LiH on the same PES and concluded that the isotope substitution has more effect on the orientation degree of the product LiF perpendicular to the scattering plane.…”
mentioning
confidence: 99%